(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the nutritional status and describe associated nutritional factors among patients with depression at the National Institute of Mental Health, Bach Mai Hospital during 2024–2025. Methods: A cross-sectional descriptive study was conducted on 121 patients, using non-probability sampling. Anthropometric measurements were performed according to WHO standards. Nutritional status was classified based on the Asian Body Mass Index (BMI) criteria. Results: Among 121 participants, the prevalence of overweight and obesity accounted for the majority (48.76%), while undernutrition was observed in 5.79% of cases. Patients living in urban areas exhibited a higher rate of severe depression (38.47%) compared to those in rural areas (5.36%) (p < 0.05). Individuals reporting high or very high work-related stress had a significantly higher prevalence of severe depression (30.12%) than those with mild or no stress (7.90%) (p < 0.05). Multivariate regression analysis revealed that age was a prominent factor associated with the severity of depression. Conclusion: Patients with depression face a double burden of malnutrition. Age, residence, and occupational stress levels are key associated factors. Nutritional and lifestyle intervention programs are necessary to improve health outcomes and enhance quality of life among patients with depression.